2019
DOI: 10.1108/emjb-03-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

Social performance of the company

Abstract: Purpose The notion of social performance of the company (SPC) is a fundamental concept of the research on ethics of business and work on company-society relationships. The study raises several debates concerning SPC’s determinants. The purpose of this paper is to provide a framework of SPC along with its social and technological determinants. After identification of the determinants, the authors have searched through a managerial perspective to recognize the effects of these determinants on SPC. Design/metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Extrinsic motivation is positively influence user intention and behavior to continue IB services (Lin et al, 2009;Standage et al, 2005). Literature supports that user feels intrinsically motivated when social activities provoke intrinsic interest which in turn positively influence user behavior and intention (Arfaoui et al, 2020;Deci and Ryan, 1985;Santoro et al, 2019). Earlier studies have established that external, internal, identified and introjected regulations have significant impact user continuance intention toward usage of IB system (Deci and Ryan, 2000;Limayem and Cheung, 2008;Lin and Anol, 2008;Lin et al, 2009;Standage et al, 2005).…”
Section: The Self-determination Theory and User Continuance Intentionmentioning
confidence: 99%
“…Extrinsic motivation is positively influence user intention and behavior to continue IB services (Lin et al, 2009;Standage et al, 2005). Literature supports that user feels intrinsically motivated when social activities provoke intrinsic interest which in turn positively influence user behavior and intention (Arfaoui et al, 2020;Deci and Ryan, 1985;Santoro et al, 2019). Earlier studies have established that external, internal, identified and introjected regulations have significant impact user continuance intention toward usage of IB system (Deci and Ryan, 2000;Limayem and Cheung, 2008;Lin and Anol, 2008;Lin et al, 2009;Standage et al, 2005).…”
Section: The Self-determination Theory and User Continuance Intentionmentioning
confidence: 99%
“…This enables schools and universities to achieve their scholarly output goals in terms of quality, impact and exposure. Also, such strategies adopted by a university can promote faculty brand (Quaratino and Mazzei, 2018), enhance the perceived social performance of the university, and lead to affective and calculated commitment (Arfaoui et al, 2019). It is worth noting that a school with a regionally oriented mission, such as AKSOB, can highly benefit from encouraging its faculty members to publish in journals such as EuroMed.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Healthcare costs are increasing more and more across all of the world’s countries and represent a significant burden on each government [ 8 ]. The multiple effects of chronic diseases on a country’s productivity and demography appears crucial for defining the performances of a national economy [ 9 , 10 ]. Tracing and investigating the characteristics of chronic diseases appears crucial for identifying the burden of disease, for better managing health services, and for assessing prevention [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%